Analisis Penerapan Pengendalian Kualitas Menggunakan Metode Lean Six Sigma pada UMKM di Tahun XYZ untuk Meningkatkan Efisiensi Produksi - Julia Novianty Shandika; Wiku Larutama; Pebi Yuda Pratama (Pusat riset dan Inovasi Nasional, 2025)
UMKM Tahu XYZ, a small-scale tofu producer, is currently facing significant challenges in maintaining consistent product quality, primarily due to a high defect rate. Common issues identified include crumbled tofu shapes, overly soft textures, and inconsistent taste, which negatively impact customer satisfaction and business sustainability. This study aims to investigate the root causes of these quality issues and propose practical solutions using the Lean Six Sigma methodology. The research employs a descriptive quantitative approach through the DMAIC framework—Define, Measure, Analyze, Improve, and Control—to ensure systematic problem-solving. Data were collected over a six-month period through direct observation, structured interviews, and review of production records. The analysis identified four dominant types of waste within the production process: unnecessary transportation, product defects, excessive movement, and over-processing. The root causes of these inefficiencies are linked to poor handling of raw materials, variability in soybean quality, and an ineffective production layout that hampers workflow and consistency. To address these problems, the study proposes several targeted interventions, including the redesign of the production layout to optimize flow, the implementation of the 5S (Sort, Set in order, Shine, Standardize, Sustain) workplace organization method, the development of standardized operating procedures (SOPs), and the adoption of improved soybean boiling technology. The implementation of these improvements is projected to significantly reduce product defects, enhance process efficiency, and ultimately increase customer satisfaction. Furthermore, these actions are expected to improve the overall competitiveness of UMKM Tahu XYZ within the highly demanding food industry sector. This research provides actionable insights for other micro, small, and medium enterprises (MSMEs) seeking to apply structured quality control methods to strengthen operational performance and long-term business resilience.